2010
DOI: 10.1111/j.1526-4610.2009.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Pathways Involvement in Children With Migraine: A Neuro‐Otological Study

Abstract: This single-blind work outlines the brain stem abnormalities in children with migraine in the form of direct involvement of peripheral or central vestibular pathways or both. Interestingly, some children with migraine but without vestibular symptoms also had abnormal results at vestibular testing. This could demonstrate a subclinical involvement of vestibular pathways without clinical presentation. The subjects are still being followed up to evaluate the evolution of symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
3
20
0
3
Order By: Relevance
“…The mean values obtained were found to be consistent with P1 (P13) and N1 (P23) values in the literature [20][21][22][23][24][25] . Berry et al 26 did not find any relationship between Tinnitus Disability Questionnaire (TDQ) scores and pure voice mean and speech discrimination scores.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean values obtained were found to be consistent with P1 (P13) and N1 (P23) values in the literature [20][21][22][23][24][25] . Berry et al 26 did not find any relationship between Tinnitus Disability Questionnaire (TDQ) scores and pure voice mean and speech discrimination scores.…”
Section: Discussionsupporting
confidence: 88%
“…In the study of Baier and Dieterich 23 where CVEP was implemented on the patients with vestibular migraine, according to the amplitudes bilateral vestibular migraine in 68% of patient in the control group it was found to be lower 6 . In the study conducted by Liao and Young 24 , unilateral or bilateral abnormal cVEMP values were found in 50% of patients with basilar migraine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent data demonstrate the potential underdiagnosed extent of MAV in children. While approximately 10% of children meet the International Headache Society criteria for migraine headache, vestibular symptoms occur in about 25% of them [19]. …”
Section: Discussionmentioning
confidence: 99%
“…40 Generally, motion sickness is more frequent in migraineurs (40-67%) than in the general population (30%). 38 Some studies have shown abnormal vestibular function in individuals with migraine [41][42][43] to include abnormal perception of upright (i.e., subjective visual vertical [SVV]), 42,44 while others showed normal vestibular function tests. 45 Children with vestibular migraine also had increased sway on condition 5 of the SOT (i.e., swayed surface with eyes closed) that was related to a diagnosis of persistent postural perceptual dizziness (3PD).…”
Section: Children With Myelomeningocelementioning
confidence: 99%